Origin and direction of replication in mitochondrial DNA molecules from the genus Drosophila. - Goddard, J M (1980)
Mitochondrial DNA (mtDNA) obtained from ovaries of Drosophila simulans, D. mauritiana, D. takahashii, D. yakuba and D. virilis was examined by electron microscopy. From a consideration of the structural properties of replicative intermediates, it was concluded that in mtDNA molecules of each species, synthesis on one strand can be up to 97% complete before synthesis on the complementary strand is initiated. MtDNA molecules of each species contain a single A+T-rich region which shows species-specific size variation from 1.0 kb (D. virilis) to 4.8 kb (D. simulans), and maps at the same position in all molecules relative to three common EcoRI sites. The structural properties of complex forms, interpreted as having originated from replicative intermediates, and produced by either partial denaturation or EcoRI digestion, are consistent with the hypothesis that replication is initiated within the A+T-rich region and proceeds unidirectionally around the molecule towards the nearest common EcoRI site. The replication origin is located near the center of the A+T-rich region in D. simulans and D. mauritiana, but lies closer to that end of the A+T-rich region which is distal to the nearest common EcoRI site in D. takahashii, D. yakuba and D. virilis.